Soil Cracking Depth as Influenced By Soil Physical Properties - Fattah, Mohammed A.; Khurshid, Shadan H.; Ahmad, Rebaz A. (Sulaimani Journal for Pure and Applied Sciences, 2018)
Knowledge of the tendency of soils to change volume as moisture content changes and regional distribution of expansive soils are of great importance. Therefore it is expected that they exhibit soil cracks. To achieve this fact, bulk soil samples were collected from the surface layer (0.00– 0.30m) of five locations that are distributed throughout the Sulaimani governorate and its surrounding. Standard procedures were applied to perform physical, chemical and geotechnical properties of the investigated soils. The effect of five soil types and four levels of normal bulk density (100, 107, 114, and 121%) on soil crack depth was analyzed by complete randomized design. 40 metal pots each with a diameter of 25cm and 23cm in height were used to carry out this study at six periods of time. The average depth of crack at several random points along the length of the cracks was measured by inserting a 2mm steel rod. Relationships among soil cracks depth with the clay content, organic matter, and liquid limit at all levels of bulk density were positive, while it was negative with sand content. Stronger correlations for all studied properties were obtained in the highest state of bulk density. As bulk density increased the difference of cracks depth decreased; when bulk density increased from 100% to 121% of the normal the soil cracks depth decreases by 28.5%. This results in clay content, sand content, liquid limits, and organic matter to have less effect on crack depth at 121% of normal state of bulk density.
Keywords: Soil crack,Bulk density,Moisture